MORCEGO (PHYLLOSTOMIDAE) NA ALIMENTAÇÃO DO LAGARTO AMEIVA AMEIVA (SAURIA, TEIIDAE) NO PARQUE ESTADUAL DOIS IRMÃOS, RECIFE/PE - Moraes, Barbara Lins Caldas de; Santos, Ednilza Maranhão dos (Revista Nordestina de Zoologia, 2012)
In this communication we report a ingestion event of the bat Phyllostomidae by the lizard Ameiva ameiva (Linnaeus, 1758) on May 26, 2010. This event occurred in an urban fragment of Atlantic forest in Parque Estadual Dois Irmãos, municipality of Recife, Pernambuco State, northeastern Brazil.